Fostering Public Trust: The Transformative Leadership of School Principals - Muhammad Hengky Wijaya; Abu Khoir; Abdul Wahid Zaini (Nurul Jadid University, 2022)
This paper describes the efforts of the head of madrasah transformational leadership in increasing public trust in MTs Al-Anwar Pancoran Bondowoso. The purpose of this research is to find out and analyze the efforts of madrasa principals in building public trust. Public Trust is the topic studied in this research because part of the things that cause it in shaping the image of the institution. This study uses a qualitative approach to the type of case study. The informants included the head of the madrasa, teaching staff, parents and students of MTs Al-Anwar Pancoran Bondowoso, through purposive sampling. The data analysis uses Miles and Huberman's concepts, namely data reduction, data presentation and conclusions or data verification. The research results obtained are the implementation of the transformational leadership of the head of the madrasa at MTs Al-Anwar, namely building teamwork by instilling the same vision and mission, building trust in subordinates, respecting and appreciating fellow employees, always providing motivation to their subordinates, a pleasant working climate, there is appreciation or rewards. With the implementation of this leadership, it has an impact on increasing public/local community trust, marked by the increasing number of new students in the new school year.